1978
DOI: 10.1071/bi9780097
|View full text |Cite
|
Sign up to set email alerts
|

Mudjinbarry Virus, an Orbivirus Related to Wallal Virus Isolated from Midges From the Northern Territory of Australia

Abstract: A virus strain (NT14952) isolated from Culicoides marksi collected in the Alligator Rivers area of the Northern Territory of Australia in September 1971 was shown to be an orbivirus anti genically related to but distinct from Wallalvirus. The name 'Mudjinbarry virus' is suggested for it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Only intra-serogroup reassortment has been reported (Gorman et al, 1978;Kahlon et al, 1983;Brown et al, 1988) and inter-serogroup reassortment was not demonstrated in reassortment experiments with EHD, bluetongue and Pata viruses (Brown et al, 1988). Experiments in progress with the Eubenangee, Wallal and Warrego serogroup viruses suggest that reassortment occurs within each serogroup, and only between isolates which exhibit high levels of sequence conservation.…”
Section: Inter-serogroup Genetic Relatednessmentioning
confidence: 96%
See 1 more Smart Citation
“…Only intra-serogroup reassortment has been reported (Gorman et al, 1978;Kahlon et al, 1983;Brown et al, 1988) and inter-serogroup reassortment was not demonstrated in reassortment experiments with EHD, bluetongue and Pata viruses (Brown et al, 1988). Experiments in progress with the Eubenangee, Wallal and Warrego serogroup viruses suggest that reassortment occurs within each serogroup, and only between isolates which exhibit high levels of sequence conservation.…”
Section: Inter-serogroup Genetic Relatednessmentioning
confidence: 96%
“…Viruses which are serologically related to Wallal have been isolated from C. dycei and C. marksi (Doherty et al, 1973;Standfast et al, 1984). A second serotype, Mudjinbarry, was isolated from C. marksi collected in the Northern Territory (Doherty et al, 1978). The Warrego serogroup viruses have been isolated from Culicoides midges, Anopheles mosquitoes and Culex mosquitoes (Doherty et al, 1973(Doherty et al, , 1979Standfast et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Wallal and Mudjinbarry viruses are serotypes of the Wallal serogroup of orbiviruses which were isolated from Culicoides spp. in northern and central Australia (5,6). The viruses share complement-fixing antigens but may be distinguished by the plaque reduction neutralization test (6).…”
mentioning
confidence: 99%
“…The related Mudjinbarry virus was isolated by Doherty et al (1978) from C. marksi collected at Mudginberri Station 170 km east of Beatrice Hill. The Beatrice Hill isolates all came from C. marksi.…”
Section: Wallal Serogroupmentioning
confidence: 99%